Potassium Fertilization of Sweet Corn in a Potassium-rich Soil - Natalia, Meneses [UNESP]; Waldir, Mendoza-Cortez Juan; Bernardes, CecilioFilho Arthur [UNESP] (Univ Republica, Fac Agronomia, 2017)
Hybrids with high yield potential and nutritional requirement, higher cost of fertilizers and environmental impact caused by the excessive use of nutrients, are factors that require improvements in the management of fertilization of sweet corn. An experiment was carried out from 24/4 to 25/8 2014, in Sao Paulo, Brazil, aiming to evaluate potassium (K) rates (0, 50, 100, 150, 200 and 250 kg ha(-1) de K2O), in the yield of supersweet corn 'GSS 41243', main cultivar used by agribusiness in Sao Paulo, Brazil.' The culture was established in a K rich Rhodic Hapludox soil (4,2 mmol(c) dm(-3) exchangeable K). Potassium rates did not influence total, commercial and grain productivities, grain yield, length and diameter of the ear, or leaf potassium content. Therefore, K fertilization in supersweet corn 'GSS 41243' in a K rich Rhodic Hapludox soil can be dispensed.
Keywords: Zea mays convar. saccharata var. rugosa; K excess; plant nutrition